Luxembourg : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Luxembourg's 2006 Article IV Consultation reports that the dominant financial sector has supported a steady rebound in economic activity. Growth is projected to remain healthy in the near term, but trend growth may decline as the rapid financial sector expansion may decelerate. The financial sector's successful shift from traditional banking services to the investment fund industry (IFI) is well advanced. The close integration of Luxembourg's mostly foreign-owned financial institutions with their parent companies tends to enhance soundness, including asset quality and capital adequacy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet